Beyond the ‘professional project’: the political positioning of Hong Kong lawyers - Lee, Karen Man Yee (International journal of law, crime and justice, 2017)
This article examines the factors underlying the political positioning of lawyers in Hong Kong. It responds to contemporary debates on the sociology of professions by arguing that the ‘professional project’ – which sees social status and market monopoly as the profession's primary goals – cannot fully explain lawyers' political behaviour under state-society dynamics. Hong Kong's case is particularly instructive. Ethnically Chinese, yet practising British common law, Hong Kong saw its sovereignty shift from Britain to China on 1 July 1997. The ideological difference between its two branches of legal professionals – barristers and solicitors – has since become more apparent. With reference to cause lawyering, this article highlights the roles of political ideology, the nature of the lawyer-client relationship and legal education in shaping the political orientation of lawyers. It offers insight into how Hong Kong's legal profession must constantly negotiate with a regime that has not traditionally championed the rule of law.